PENGGUNAAN MEDIA FOTO DAN GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI PENINGGALAN SEJARAH DAN TOKOH SEJARAH ISLAM DI INDONESIA - Ahmad Agus Gustaman (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2021)
Lack of interest in learning about historical heritage materials and Islamic historical figures in Indonesia. This can be seen from the learning achievement of students who are less than the KKM as many as 59.38%. Researchers use photo and image media to improve student learning outcomes, because photo and image media are concrete so students will be able to see clearly what is being discussed. This Classroom Action Research uses John Elliot's CAR Model, covering 2 cycles, each cycle consisting of four stages, namely: planning, implementing, observing, and reflecting. The research location is in SMP Negeri 1 Margahayu Kab. Bandung. The object of research is the students of grade 9 J, totaling 40 people. The results showed that in the pre-cycle of students who scored above the KKM (completed) there were 18 people with an average score of 64.87 or 45% of all students. In the first cycle of students who are above the KKM score as many as 22 people with an average value of all students 72.37 or 62.5%, in the first cycle there is an increase of 17.5% from the completion of pre-cycle activities. Then the average value in the second cycle of students who completed reached 40 people with an average value of 79.5 students who achieved 100% completeness, were in very good qualifications and experienced an increase of 37.5% from cycle I. This shows increasing student learning outcomes on historical heritage materials and Islamic historical figures in Indonesia.